1999
DOI: 10.3354/meps177235
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory foraging in Antarctic seabirds:a species-specific attraction to krill odors

Abstract: Antarctic procellariiform seabirds are known for their well-developed sense of smell, yet few behavioral experiments have addressed how these birds use olfactory cues to forage at sea. I describe results from controlled, shipboard experiments performed in Antarctic waters near Elephant Island. Birds were presented with plain or krill-scented (Euphausia superba) vegetable oil slicks, and their behavioral responses were compared. Krill-scented vegetable oil slicks were highly attractive to some but not all proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 18 publications
3
58
0
1
Order By: Relevance
“…Thewissen et al (2011) hypothesize that bowheads, Balaena mysticetus use olfaction to detect conspecific mates and/ or more likely clouds of the plankton on which they feed. Evidently, krill give off a peculiar odor, partly caused by dimethylsulfide and pyridines (Nevitt, 1999). Minke whales have a much more diverse diet (Perrin et al, 2009), in which case, if they are using olfaction in their pursuit of prey, it is not known what (other) airborne cues they are responding to.…”
Section: Discussion On the Identity Of Cmm-v-4536mentioning
confidence: 99%
“…Thewissen et al (2011) hypothesize that bowheads, Balaena mysticetus use olfaction to detect conspecific mates and/ or more likely clouds of the plankton on which they feed. Evidently, krill give off a peculiar odor, partly caused by dimethylsulfide and pyridines (Nevitt, 1999). Minke whales have a much more diverse diet (Perrin et al, 2009), in which case, if they are using olfaction in their pursuit of prey, it is not known what (other) airborne cues they are responding to.…”
Section: Discussion On the Identity Of Cmm-v-4536mentioning
confidence: 99%
“…Thus, seabirds appear to make hierarchical decisions -first to find large-scale and then to locate small-scale habitat features that aggregate prey (Russell et al 1992, Weimerskich et al 1997, Nevitt & Veit 1999, Fauchald et al 2000. Cues that may help seabirds select profitable foraging habitat and then prey within that habitat include water temperatures (Ribic & Ainley 1997), thermal fronts (Hoefer 2000), pycnocline depth (Ribic & Ainley 1997), olfactory cues (Nevitt 1999), the presence of other birds (Lachmann et al 2000), and the ability to visually locate prey (Gaston & Jones 1998). During the breeding season, nesting seabirds have the additional energetic constraint of traveling between colonies and foraging sites (Hull et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that seabirds are predictably concentrated at physical oceanographic features of different spatial scales, from tidal fronts through mesoscale eddies to latitudinal frontal systems, which all display increased prey availability (Haney et al 1995, Pakhomov & McQuaid 1996, Rodhouse et al 1996, Hunt et al 1999. Once at an area of enhanced biological productivity, procellariforms may use odor trails or visual clues to locate concentrations of prey (Nevitt 1999).…”
Section: Introductionmentioning
confidence: 99%